Practical criteria for a safer liposuction: a multidisciplinary approach - Julio Wilson Fernandes; Arnaldo Miró; Andréa Amorim de Séllos Rocha; Célio Teixeira Mendonça; Claudio Luciano Franck; William Massami Itikawa (Revista Brasileira de Cirurgia Plástica, 2017)
In 2012, the Research Group on Body Contouring Surgery of the Brazilian Society of Plastic Surgery conducted an extensive study on the safety of liposuction before the initiation of the course of the Group, held in 2013 in Rio de Janeiro during the 50th Brazilian Congress of Plastic Surgery, with the presence of the illustrious Dr. Yves Gérard Illouz and a large number of participants. The authors performed a review and update of the safety parameters, incorporating recent advances and systematizing relevant information for the execution of a safer liposuction. With the collaboration of anesthesiologist, intensive care physician, and vascular surgeon, all with extensive experience in supporting the procedure, new practical guidelines were presented for a safer liposuction on the preoperative, transoperative, and postoperative periods.